Subclinical myocardial injury in ATTR-related familial amyloid polyneuropathy patients without clinical signs of cardiomyopathy. (3rd October 2022) - Nicolela Geraldo Martins, C; Paim, L R; Da Silva, L M; Scriptori, G; Bau, A A; Coy-Cangucu, A; Yamaguti, R; Franca Nunes, R F; Franca Jr, M; Neilan, T; Jerosch-Herold, M; Coelho-Filho, O
Abstract: Background: ATTR-related Familial Amyloid Polyneuropathy (FAP) is a hereditary disease that primarily affects peripheral nerve function. Few studies have investigated cardiac involvement and myocardial tissue remodeling in FAP. Aim: To investigate subclinical myocardial tissue remodeling in FAP patients without cardiomyopathy using a multiparametric CMR protocol. Results: Thirty-one FAP patients (46.9±16.1 years, 57% female, 60% Val30Met mutation) and 33 healthy controls (41.3±13.7 years, 58% female) were enrolled, undergoing a multiparametric CMR protocol for assessment of ventricular morphology and function, native myocardial T1, extracellular volume fraction (ECV) and intracellular lifetime of water). Cardiopulmonary exercise capacity was evaluated with a cycle ergometer. Cardiac high-sensitive troponin T (cTnT) and NT-proBNP were measured to assess for cardiac injury. The majority of ATTR-PN patients were in stage 1 (70%) with mild symptoms of sensory, motor and autonomic neuropathy. Adjusted maximum oxygen consumption was reduced among FAP patients compared to healthy controls (FAP: 22.2±8.2 mL/kg/min vs. controls: 30.3±10.2 mL/kg/min, p<0.001). Although none of FAP patients reported heart failure symptoms, NT-proBNP (FAP: 251.240±624.446 ng/dL, vs. controls: 34.3±29 ng/dL, p<0.005) and cTnT (FAP: 13.2 [3.0, 19.0] ng/dL, vs. controls: 3.6 [3.0, 6.0] ng/dL, p<0.005) were elevated, and both correlated with ECV (cTnT: R=0.81, P<0.001; NT-proBNP: R=0.61, P=0.001, Fig. 1). While LVEF was preserved among FAP patients (FAP: 67.9±8.2% vs. controls: 65.4±4.3%, p=NS), LVmass index was increased compared to control subjects (FAP: 58.5±18.8 vs. and controls: 42±9.2 g/m 2, p<0.005). Both native T1 (FAP: 1, 303.924±120.152, vs. controls: 1, 212.78±76.01 ms, p<0.05) and ECV (FAP: 0.36±0.1, vs. controls: 0.26±0.02, p<0.001) were markedly elevated among FAP patients. In contrast the intracellular lifetime of water, a validated marker of cardiomyocyte size was reduced in the FAP group (FAP: 0.082±0.04 vs. controls: 0.14±0.05, p<0.001). There was a trend for ECV to increase linearly with FAP stage, and native T1 trended higher in stage 1 and 2 patients compared to stage 0. Both ECV (R=0.89, p<0.001) and native T1 (R=0.62, p<0.001) were correlated with LVmass index (Fig 2). Conclusion: In FAP without clinical signs of cardiac involvement, significant extracellular matrix expansion was present. The increase of LV mass in these patients is associated with expansion of the extracellular matrix, possibly as a result of diffuse replacement fibrosis, and below-normal cardiomyocyte diameter. These findings from serum biomarkers and CMR tissue phenotyping provide evidence of sub-clinical cardiac involvement through adverse myocardial tissue remodeling in FAP patients presenting with mostly mild symptoms of peripheral neuropathy. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Pfizer